Mesh generation and refinement in 2D modelling. A case study - Pinho, José L. S. (1999)
Ria de Arosa is a bay located in the western region of Galicia-Spain, and is a well-known producer of commercially valuable shellfish, especially by raft culture of the edible mussel. Due to the ever increasing of sediments concentration in the water column, mussel productivity has been lowered in the past years. A research project on information systems for water quality assessment in that coastal zone is being developed at the University of Minho for decision making support. Two numerical solvers of the shallow water equations based on the finite element method (FEM) were used for hydrodynamic simulations. This paper describes the general framework to generate meshes for simulations and presents the principal characteristics of a mesh generator that produces exact Delaunay triangulations, constrained Delaunay triangulations, and quality conforming Delaunay triangulations. A method for conditioned mesh refinement is also presented, where several area constraint criteria related to water depth, velocity gradients, and pollutant concentration gradients can be established.